Search for top-squark pairs decaying into Higgs or Z bosons in pp collisions at $\sqrt{s}$=8 TeV - CMS collaboration (2135 authors); Hollar, Jonathan; Nayak, Aruna; Calpas, Betty; Bargassa, Pedrame; Beirão Da Cruz E Silva, Cristóvão; Faccioli, Pietro; Ferreira Parracho, Pedro Guilherme; Gallinaro, Michele; Nguyen, Federico; Rodrigues Antunes, Joao; Seixas, Joao; et al. (My University, 2014)
A search for supersymmetry through the direct pair production of top squarks, with Higgs (H) or Z bosons in the decay chain, is performed using a data sample of proton-proton collisions at sqrt(s) = 8 TeV collected in 2012 with the CMS detector at the LHC. The sample corresponds to an integrated luminosity of 19.5 inverse femtobarns. The search is performed using a selection of events containing leptons and bottom-quark jets. No evidence for a significant excess of events over the standard model background prediction is observed. The results are interpreted in the context of simplified supersymmetric models with pair production of a heavier top-squark mass eigenstate stop[2] decaying to a lighter top-squark mass eigenstate stop[1] via either stop[2] to H stop[1] or stop[2] to Z stop[1], followed in both cases by stop[1] to t neutralino, where neutralino is an undetected, stable, lightest supersymmetric particle. The interpretation is performed in the region where the mass difference between the stop[1] and neutralino states is approximately equal to the top-quark mass (m[stop[1]] - m[neutralino] ~= m[t]), which is not probed by searches for direct stop[1] squark pair production. The analysis excludes top squarks with masses m[stop[2]] < 575 GeV and m[stop[1]] < 400 GeV at a 95% confidence level.